Profile of Risk Factors for Hemorrhagic Stroke in Patients at the Neurological Inpatient Installation of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from January to June 2022 - Surdji, Almuta'Aaliyati Nur; Ardhi, Mohammad Saiful; Parenrengi, Muhammad Arifin; Setyowatie, Sita (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: Modifiable risk factors of hemorrhagic stroke were hypertension, DM, dyslipidemia, and smoking history. Non-modifiable risk factors of hemorrhagic stroke were gender and age.   Abstract Introduction: Stroke is one of the top ten causes of death worldwide. Hemorrhagic strokes are more common in men, and their risks increase with age. This study aimed to determine the risk factor profile for hemorrhagic stroke (intracerebral hemorrhage/ICH and subarachnoid hemorrhage/SAH) among patients in the neurological inpatient installation of Dr. Soetomo General Academic Hospital, Surabaya, from January to June 2022. Methods: This study employed a descriptive observational method, utilizing secondary data obtained from the medical records of patients with hemorrhagic stroke at Dr. Soetomo General Academic Hospital, Surabaya, from January to June 2022. The data calculations were performed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26. The variables examined in this study included the type of hemorrhagic stroke, non-modifiable risk factors, modifiable risk factors, and other risk factors. Results: In total, 50 medical records were retrieved. The type of hemorrhagic stroke was dominated by intracerebral hemorrhage. Among them, 29 (58%) patients were males, 35 (70%) patients were 46-65 years old, 41 (82%) patients had hypertension, 16 (32%) patients had diabetes mellitus (DM), 19 (38%) patients had dyslipidemia, 8 (16%) patients had a history of smoking, 14% of patients had aneurysms. Only 2% of patients had arteriovenous malformation (AVM). Conclusion: The dominant risk factors for hemorrhagic stroke were gender, age 46-65 years old, and hypertension.